2017
DOI: 10.1111/srt.12408
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of measurement of skin melanin, total hemoglobin, and oxygen saturation

Abstract: In the recently published study by Nkengne et al, 1 a new technology for the automated quantification of skin melanin, total hemoglobin, and oxygen saturation was investigated. In specific, the reproducibility and repeatability of a hyperspectral imaging device and software (SpectraCam ® ) was studied. The system and the determined parameters related to skin chromophores are very promising and useful especially in cosmetology.In respect to the analysis of the reproducibility and repeatability of quantitative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Skin pigmentation, or, as some refer to it, skin tone or skin color, is a factor that may affect measured SpO 2 values [9,10], with dark pigmentation reported to cause detection errors [11]. This is in part related to the dependence of the detected light intensity on melanin absorption patterns and wavelengths [12,13]. Furthermore, other studies reported that SpO 2 values determined by pulse oximetry overestimate true SaO 2 values in persons with darkly pigmentated skin [14,15], although some reports indicate either overestimation or underestimation in persons of color [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Skin pigmentation, or, as some refer to it, skin tone or skin color, is a factor that may affect measured SpO 2 values [9,10], with dark pigmentation reported to cause detection errors [11]. This is in part related to the dependence of the detected light intensity on melanin absorption patterns and wavelengths [12,13]. Furthermore, other studies reported that SpO 2 values determined by pulse oximetry overestimate true SaO 2 values in persons with darkly pigmentated skin [14,15], although some reports indicate either overestimation or underestimation in persons of color [16,17].…”
Section: Introductionmentioning
confidence: 99%